2018
DOI: 10.15713/ins.jmrps.137
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell fibroma: A case report with review of literature

Abstract: Benign gingival overgrowths are not uncommon in the oral cavity. Reactive lesions and neoplasms comprise the spectrum of local proliferations that occur in the gingiva. Similarity in the clinical features of these diverse lesions further compound the dilemma in arriving at a proper clinical diagnosis. Giant cell fibroma (GCF) is one such interesting lesion that may clinically mimic a fibroma or a papilloma that can only be diagnosed after histopathological examination from its unique and characteristic feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…10 While GCF, unlike other fibrous overgrowths, appear benign despite having the peculiarly manifest giant fibroblasts in the stroma, their clinical presentation and histology are the same as the vast bulk of non-neoplastic lesions in the oral cavity. 11 According to multiple reports, the etiology of GCF suggests that minor trauma can induce the lesion to develop, and that it is marked by functional changes in fibro-blastic cells. 12 Histopathological examination of GCF reveals distinctive multiple large stellate-shaped and occasionally multi-nucleated fibroblasts sparsely arranged in a fibrous connective tissue with large nuclei and thin elongated cytoplasmic processes.…”
Section: Discussionmentioning
confidence: 99%
“…10 While GCF, unlike other fibrous overgrowths, appear benign despite having the peculiarly manifest giant fibroblasts in the stroma, their clinical presentation and histology are the same as the vast bulk of non-neoplastic lesions in the oral cavity. 11 According to multiple reports, the etiology of GCF suggests that minor trauma can induce the lesion to develop, and that it is marked by functional changes in fibro-blastic cells. 12 Histopathological examination of GCF reveals distinctive multiple large stellate-shaped and occasionally multi-nucleated fibroblasts sparsely arranged in a fibrous connective tissue with large nuclei and thin elongated cytoplasmic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present study, several studies have indicated that the lesion is usually less than 1 cm in diameter (4,7). With regard to the origin of giant cell fibroma, immunohistochemical analysis has shown positive staining of stellate and multinucleated cells with vimentin and prolyl-4-hydrolase, suggesting that these cells might originate from fibroblasts (8,9). Ultrastructural studies have revealed numerous intracellular microfibrils supporting the fibroblastic nature of the giant cells in the lesion (10).…”
Section: Discussionmentioning
confidence: 99%
“…Ultra structurally, multinucleated giant cells were fibroblasts [13] . Immunohistochemistry reveals a positive response to vimentin and prolyl-4-hydrolase thus suggesting it as a phenotypically fibroblastic origin [1] . Cytokeratin, neurofilament, HHF, CD 68, HLA DR, Tryptase, and S-100 protein showed negative reactivity.…”
Section: Introductionmentioning
confidence: 97%
“…This oral tumor was first described by Weather and Callihan in 1974 as a separate category of fibroma who found 108 unique entities among 2000 fibrous hyperplastic lesions because of its distinct histopathological appearance and therefore does not is considered it as conventional fibroma [1] . It was designated as Giant cell fibroma (GCF) because of the characteristic presence of stellate fibroblasts with multinucleated giant cells histopathologically [2,3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation